Childhood harsh discipline and behavioral problems: the mediating roles of attachment dimensions - Won, Ying Qing (2025)
Background: Parental harsh discipline (i.e., psychological aggression and physical discipline) has been consistently associated with greater child behavioral problems. Yet the mechanism underlying this association remains unclear. Harsh discipline may not have similar negative implications in cultures where it is prevalent. Objective: This study examined the direct associations between childhood harsh discipline and behavioral problems, as well as the mediating roles of attachment dimensions (i.e., trust, communication, alienation) in these relationships. Participants and setting: 449 Singaporean young adults completed the survey (Mage = 22.57, SDage = 1.77, 52% female). Methods: Participants reported on their childhood discipline, current attachment towards their parent, and current behavioral (i.e., externalizing and internalizing) problems. Path analyses were conducted separately for mothers and fathers. Results: Maternal psychological aggression and parental severe physical discipline were directly related to greater externalizing problems. Parental psychological aggression and maternal severe physical discipline were indirectly associated with greater behavioral problems through alienation. The relationship between paternal psychological aggression and externalizing problems was also mediated by poor communication. Null finding for minor physical discipline was observed. Conclusions: Psychological aggression and severe physical discipline are related to greater behavioral problems, even in a cultural context where strict discipline is deemed acceptable. Minor physical discipline may have less adverse consequences in such a context. Parental alienation and paternal poor communication were the intervening mechanisms through which psychological aggression and severe physical discipline are related to greater behavioral problems. These findings highlight the need to encourage non-violent disciplinary strategies to facilitate optimal child development.